Redefining Normative Standards for Pro-Environmental Action: The Role of Dynamic Norms in Promoting Pro-Environmental Organizational Citizenship Among Workers in Metropolitan Lima (Palimpsesto, 2025)
This qualitative study explores beliefs and attitudes about environmental pollution and plastics, investigating the role of organizations and collaborators through 22 interviews with workers in Lima. The results reveal paradoxes between environmental knowledge, emotional responses, and concrete actions. Patterns such as “paralysis by analysis” are identified in organizations with high environmental awareness, and “transformational pragmatism” in traditional organizations, where dynamic norms generate greater individual environmental commitment. The research suggests that these norms work best when pro-environmental behaviors emerge as spontaneous tendencies, not as moral imperatives, providing a new approach to fostering pro-environmental organizational citizenship.
Keywords: Pro-environmental behavior; Organizational citizenship; Dynamic norms